2011
DOI: 10.1111/j.1740-0929.2010.00861.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cellooligosaccharide or synbiotic feeding on growth performance, fecal condition and hormone concentrations in Holstein calves

Abstract: We investigated the effect of cellooligosaccharide (CE) or a combination of dextran and Lactobacillus casei ssp. casei strain JCM1134(T) (synbiotic; SB) feeding on growth performance, fecal condition and hormone concentrations in Holstein calves. Fifty-two female Holstein calves were randomly assigned to three treatment groups: CE feeding group (n = 16), SB feeding group (n = 18), and control group (n = 18). Body weight at 90 days of age, as well as daily body weight gain (DG) and feed efficiency after weaning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 26 publications
0
34
1
2
Order By: Relevance
“…A previous in vivo study (Hasunuma et al . ) showed that CE feeding improved ADG and feed efficiency in calves during the post‐weaning period, mainly due to enhanced production of short‐chain fatty acids by rumen microbiota. Stimulation of the intestinal flora in calves may further improve growth performance at an older age.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous in vivo study (Hasunuma et al . ) showed that CE feeding improved ADG and feed efficiency in calves during the post‐weaning period, mainly due to enhanced production of short‐chain fatty acids by rumen microbiota. Stimulation of the intestinal flora in calves may further improve growth performance at an older age.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we have observed that CE is effective when provided to weaned calves, possibly as a result of improved rumen function (Hasunuma et al . ). Improving the ability of weaned calves to digest forage may be an ideal method for increasing weight gain.…”
Section: Introductionmentioning
confidence: 97%
“…A low‐concentration dose of cello‐oligosaccharides to plant elicits an immune response and increases resistance towards diseases . Animal studies have shown that adding cello‐oligosaccharides to the feed of calves causes fewer incidences of gastrointestinal infections and reduces the use of antibiotics . Cello‐oligosaccharides also have the potential to act as a non‐digestible prebiotic that can reduce the risk of lifestyle diseases in humans by promoting the growth of beneficial bacteria and inhibiting pathogenic bacterial species in the gastrointestinal tract .…”
Section: Figurementioning
confidence: 99%
“…[2] Animals tudies have shown that adding cello-oligosaccharides to the feed of calves causes fewer incidences of gastrointestinal infections and reduces the use of antibiotics. [3] Cello-oligosaccharides also have the potentialt oa ct as an ondigestible prebiotic that can reduce the risk of lifestylediseases in humansb yp romoting the growth of beneficial bacteria and inhibiting pathogenic bacterial speciesi nt he gastrointestinal tract. [1b, 4] Thus, cello-oligosaccharides can provide multiple benefits to the agriculturala nd healthcare industries.…”
mentioning
confidence: 99%
“…TNF-α and other cytokines activate NFκB, a transcription regulator that is activated by various intra and extra cellular stimuli. TNF-α induced inflammatory responses in cattle has been well documented 6,7. To further investigate the potential role of α-tocopherol in maintaining immuno-homeostasis in bovine cells, we undertook in vitro experiments using recombinant TNF-α as an immuno-stimulant to imitate inflammation response in cells with or without α-tocopherol pre-treatment.…”
Section: Introductionmentioning
confidence: 99%